2019
DOI: 10.1111/chd.12745
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health record associated stress: A survey study of adult congenital heart disease specialists

Abstract: Background: Physician burnout has many undesirable consequences, including negative impact on patient care delivery and physician career satisfaction. Electronic health records (EHRs) may exacerbate burnout by increasing physician workload.Objective: To determine burnout in adult congenital heart disease (ACHD) specialists by assessing stress associated with EHRs.Design: Electronic survey study of ACHD providers. Setting: Canada and United States.Participants: Three hundred eighty-three ACHD specialists listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…Nine studies discussed the consequences of EHR burnout; namely, that physicians could not provide quality care, which ultimately results in global degradation of the quality of care [4,5,13,19,20,25,[31][32][33]. Burnout affects physicians' behavior [31], including that some burned-out physicians may behave unprofessionally towards their colleagues [11,28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies discussed the consequences of EHR burnout; namely, that physicians could not provide quality care, which ultimately results in global degradation of the quality of care [4,5,13,19,20,25,[31][32][33]. Burnout affects physicians' behavior [31], including that some burned-out physicians may behave unprofessionally towards their colleagues [11,28].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies discussed the consequences of EHR burnout; namely, that physicians could not provide quality care, which ultimately results in global degradation of the quality of care [4,5,13,19,20,25,[31][32][33]. Burnout affects physicians' behavior [31], including that some burned-out physicians may behave unprofessionally towards their colleagues [11,28]. Additionally, burnout affects the health of the physician [31].Physicians experiencing burnout are more likely to have mental problems, including depression, which can lead to suicide [25,28,33].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 In an observational survey study, Marckini et al found that there was high disagreement that EHR improved efficiency and patient care. 48 These studies suggest that EHR implementation has negatively changed clinical workflow. Four papers focused on how the EHR impacts clinicians' workload.…”
Section: Time Burden (N ¼ 15)mentioning
confidence: 99%